Improving your cornering - Overland, T. (1999)
Cornering skills are a very important part of speed skating technique. In short track, they are probably the most important factor for successful performance. In long track, especially so now with the fast ice on the indoor rinks, they are also of crucial importance. Improving your corner technique in the off-season, then, is a good goal for the summer training period. Ways are shown how to do this?